The theocratic State model proposed from Cumandá by Juan León Mera: characteristics and contradictions - Orihuela Oropeza, Lourdes Melisse (2024)
Juan Leon Mera was a conservative and fervently Catholic Ecuadorian writer who lived in the mid-nineteenth century whose most famous novel was “Cumandá”. In this novel, although its sentimental and Indianist aspects are usually studied, Mera concretized his ideals of a state based on Catholicism. However, this article questions whether this proposal of Catholic organization is viable at the end of the book. In this sense, it is intended, on the one hand, to characterize the elements that make up the theocratic state project and, on the other hand, to demonstrate that the conformation of this Christian and at the same time conservative project, from what is proposed in Cumandá and its relationship with the socio-political context of the time, ends up being an unviable project. The reason for this unviability is initially due to the contradiction between Juan León Mera’s condition as a representative of the conservative oligarchy of his time and the strong religious idealism far removed from the material that is perceived in his novel. On the other hand, the most important contradiction would be found in the end of the novel because, despite the conversion to Catholicism of several indigenous characters and the sacrifice of Cumandá, society ends up being the same. Only at a supraterrestrial level would there be a true resolution for the conformation of a society of such characteristics.